Fentanyl-induced chest wall rigidity in critically ill patients: A report of two cases - Apiradee Sanlee; Panadda Panusitthikorn; Pitchaya Dilokpattanamongkol; Ranistha Ratanarat (Clinical Critical Care, 2026)
Background: Fentanyl is widely used for analgesia and sedation in critically ill patients. Fentanyl-induced chest wall rigidity, also called wooden chest syndrome, is an uncommon but potentially life-threatening adverse effect that can markedly impair ventilation. Most reports involve pediatric or peri-anesthetic settings, whereas adult intensive care unit (ICU) presentations remain underrecognized. Case presentation: We describe two adults in whom fentanyl-induced chest wall rigidity was considered during mechanical ventilation. A 76-year-old man with severe chronic obstructive pulmonary disease and end-stage kidney disease developed abrupt patient-ventilator dyssynchrony and markedly reduced delivered tidal volumes after several days of fentanyl infusion, when neuromuscular blockade was withdrawn. No alternative mechanical or pulmonary cause was identified at the bedside. Ventilation improved after fentanyl discontinuation and naloxone administration. A 75-year-old man with myelodysplastic syndrome and cirrhosis developed similar dyssynchrony after cisatracurium discontinuation while receiving fentanyl. Respiratory mechanics improved after fentanyl was stopped and neuromuscular blockade was resumed. Conclusion: In mechanically ventilated patients receiving fentanyl, otherwise unexplained patient-ventilator dyssynchrony, elevated airway pressure, or a sudden reduction in delivered tidal volume should prompt consideration of fentanyl-induced chest wall rigidity. Immediate bedside assessment should exclude endotracheal tube or circuit problems, mucus plugging, pneumothorax, and bronchospasm. Prompt fentanyl discontinuation, titrated naloxone, and temporary neuromuscular blockade when ventilation remains inadequate may rapidly restore effective ventilation.